AN INVESTIGATION INTO EMOTION METAPHORS IN ENGLISH AND VIETNAMESE - TRẦN VĂN HẢI (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis focuses on investigating the conceptual metaphors expressing two abstract concepts love and happiness in English and Vietnamese on the background knowledge of cognitive semantics raised by Kӧvecses.Z in his book Metaphor: A Practical Introduction (2010). Among three types of conceptual metaphors, the research paper just concentrates on the structural metaphors expressing romantic love and happiness such as LOVE IS JOURNEY, LOVE IS A NUTRIENT, LOVE IS A UNITY, LOVE IS FIRE, LOVE IS MOTION, LOVE IS A PLANT,… and HAPPINESS IS UP, HAPPINESS IS LIGHT, HAPPINESS IS VITALITY, HAPPINESS IS A FLUID, HAPPINESS IS A NATURAL FORCE, HAPPINESS IS AN OBJECT, … in English and Vietnamese based on the descriptive approach. Then, the similarities and differences between the conceptual metaphors expressing these two abstracts in English and Vietnamese are also analyzed and displayed through the comparative analysis of about 670 samples collected from novels and short stories. This investigation can contribute some implications for English teaching and learning as well as translation work in Vietnam.